MỘT SỐ ĐẶC ĐIỂM ĐỊA CHẤT PLIOCEN - ĐỆ TỨ, ĐỊA CHẤT CÔNG TRÌNH KHU VỰC MIỀN TRUNG VÀ ĐÔNG NAM THỀM LỤC ĐỊA VIỆT NAM - Tân, Mai Thanh; Tỵ, Phạm Văn; Bát, Đặng Văn; Bách, Lê Duy; Biểu, Nguyễn; Nghi, Trần; Dung, Lê Văn (Vietnam Journal of Earth Sciences, 2011)
Characteristics of Pliocene - Quaternary geology and Geoengineering in the Center and Southeast parts of Continental Shelf of Vietnam Vietnam has a large continental shelf with complicated geological characteristics. The study of the Pliocene- Quaternary sediments is very important for understanding the shallow geological characteristics, potential of mineral resources, as well as the evaluation of offshore construction sites conditions. By the combination of HRS, 2-D, 3-D seismic and other geological methods, the detailed investigating results of the Pliocene - Quaternary formations in the Center and Southeast parts of continental shelf of Vietnam have been obtained. In this paper, the authors present the research results of establishing the structural maps, determining the sedimentary system tracts and sequences, the relationship between sedimentary cycles, sea level change and tectonic movement, facial-paleogeographic characteristics, geological development history and characteristics of engineering geology Pliocene - Quaternary.